The menopause solution - Faubion, Stephanie S. (Time Inc. Books, 2016)
"Women are spending an unprecedented one-third of their life spans in menopause, experiencing these common symptoms and changes in record numbers. This essential guide debunks the myth that what works for one will work for all. With an in-depth look at lifestyle strategies, over-the-counter medications, nutritional supplements and hormone therapy, you'll find a reliable and balanced approach for taking charge of your own health and getting the best care from your health care provider as you navigate this transition,"--page [4] of cover.